Preoperative [68Ga]Ga-FAPI-04 PET for evaluating pathological complete response to neoadjuvant therapy in gastrointestinal adenocarcinoma patients - Zhang, Xiao; Feng, Yuan; Lin, Zhaoguo; Chen, Ranran; Gai, Yongkang; Qin, Chunxia; Lan, Xiaoli (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to assess the value of preoperative [68Ga]Ga-FAPI-04 positron emission tomography (PET) for evaluating pathological complete response (pCR) in patients with gastrointestinal adenocarcinomas receiving neoadjuvant therapy (NAT).Materials and MethodsA retrospective analysis was conducted on patients with gastrointestinal adenocarcinomas who received [68Ga]Ga-FAPI-04 PET/MR scans between February 2021 and January 2024. The enrolled patients had completed preoperative NAT, undergone contemporary enhanced CT or MR scans, and received surgery within one month after PET imaging. Clinical data, imaging evaluations, PET parameters (standardized uptake values [SUVs], SUVs standardized by lean body mass [SUL], FAPI-positive tumor volume [FAPI-PTV], and total lesion burden [FAPI-TL]), and surgical pathology results were collected. Each parameter’s sensitivity, specificity, and diagnostic cutoff for predicting pCR were determined via receiver operating characteristic curve analysis. Logistic regression analysis identified independent predictors of pCR.ResultsSixty-five patients were enrolled, and 22 patients achieved pCR according to surgical pathology. In visual evaluation, [68Ga]Ga-FAPI-04 PET was limited in its ability to assess pCR, with 16 false positives and 1 false negative. The dichotomization using the FAPI-PTV cutoff value (<1.92 cm3) improved the specificity for predicting pCR to 72.7%, while retaining a high sensitivity of 93.0%. Enhanced CT or MR scans had the sensitivity and specificity of 72.7% and 93.0% in predicting pCR, respectively. According to the logistic regression analysis, a FAPI-PTV<1.92 cm3 was an independent predictor for patients who achieved a pCR (p<0.05).Conclusion[68Ga]Ga-FAPI-04 PET shows promise in predicting pCR among patients with gastrointestinal adenocarcinomas following NAT. FAPI-PTV derived from [68Ga]Ga-FAPI-04 PET may provide an effective clinical tool for guiding further treatment.